Diffusion rate of quercetin from chitosan-TPP nanoparticles dispersion of onion (Allium cepa L.) ethanol extract in medium phosphate buffer pH 7.4 - Anisa Amalia; Rahmah Elfiyani; Putri Ulan Sari (Pharmaciana, 2022)
Onion extract contains quercetin, which has anti-inflammatory properties. The absorption of quercetin in the extract can be improved by using the ionic gelation method to composition the extract into a nanoparticle system. Chitosan is a polymer that is used to make nanoparticles that impact medicinal drug absorption. Although many studies of nanoparticle coatings with chitosan have been performed, the effect of the chitosan concentration used remains an intriguing research issue, especially as a natural compound carrier.Â  The goal of this study was to examine how varying chitosan polymer concentrations affected the rate of quercetin diffusion from onion (Allium cepa L.) ethanol extract nanoparticles. With 0.1% tripolyphosphate (TPP) as a crosslinker, the concentrations of chitosan used were 0.1% (F1), 0.2% (F2), 0.3% (F3), and 0.4% (F4). Organoleptic test, particle size measurement, zeta potential, polydisperse index, entrapment efficiency, density, and determination of quercetin diffusion rate using a phosphate buffer medium pH 7.4 were all used to analyze each composition. Transparent yellow nanoparticles with particle sizes ranging from 199.89 nm to 514.97 nm, a zeta potential of 47.73 mV to 51.36 mV, a polydispersity index of 0.57, an entrapment efficiency of 54.78 % to 59.06 %, and a density of 1.012 g/mL to 1.042 g/mL are the result of this system. In each composition, the rate of diffusion follows the Higuchi reaction kinetics. Increased chitosan concentration decreases the diffusion rate of onion ethanol extract nanoparticles (Allium cepa L). The fastest diffusion rate value with requirements-meeting physical properties was obtained in nanoparticle systems containing a 0.1 % chitosan solution.Â